Dynamic measurements using digital image correlation. Issue 1 (8th February 2017) - Murray, Chris A.; Hoult, Neil A.; Take, W. Andy
Abstract : Digital image correlation (DIC), which enables non-contact measurement of displacements and strains, has seen widespread adoption within the geotechnical physical modelling community for the measurement of static displacements. Advances in high temporal resolution cameras now permit the use of DIC to calculate accelerations. However, it is currently unclear how the image acquisition rate and the choice of DIC algorithm influence the quality of this data. This paper describes the sources of error that affect the dynamic measurement accuracy. Numerical and physical experiments are used to demonstrate the relevance of ( a ) bias error in the sub-pixel interpolation scheme, ( b ) the ratio of sample rate to the frequency of the signal being monitored and ( c ) the signal-to-noise ratio on the accuracy and precision of DIC acceleration measurements. The results demonstrate that by using appropriate image texture, sampling frequencies and signal-to-noise ratios, measurements with an accuracy similar to accelerometers can be achieved. The displacement measurement error due to bias errors was found to be 0·0015 pixels. The error in the calculated velocity and acceleration was a function of the amplitude of displacement measurements with an optimum ratio between the sampling frequency to the signal frequency found to be between 25 and 50.